Best Practices for Enhancing Student Metacognitive Skills through Innovative Teaching Strategies - Sanjaya, Iksan; Syam, Rahmat Hidayat; Djide, Slamet Riyadi; Nisaa, Imamun (Educia Journal, 2024)
In this study, effective, efficient, and impractical method of cultivating metacognition in learners, such as strategy, difficulty level, and feedback system, are investigated as part of a qualitative analysis. Using semi structured interviews, focus group discussion and classroom observation research data was collected from 15 educators and 30 students of different class levels. Thematic analysis was employed to identify patterns, resulting in four key themes: these issues as metacognitive strategies, students’ engagement, factors inhibiting implementation of metacognition strategies, and feedback. The research presented in this paper shows that the approaches which foster guided reflection, self- assessment, peer cooperation, as well as the forms of scaffolded learning have a positive impact on the development of metacognitive skills. Teachers also insisted that feedback is useful as a metacognitive strategy for enhancing students’ thinking skills and raising autonomy levels. Nevertheless, some constraints including restricted time for instructions, fixed curriculum and diverse students’ learning achievements were reported as the factors which hinder the proper utilization of these strategies. The study filled the gap identified in the literature review by offering concrete, contextualised suggestions on how metacognition may be enacted in a specific institutional and timetabled context, as well as how students may be supported in terms of the institutional structures necessary for metacognition to flourish. This provides further evidence of the need for preservice and inservice teacher education and professional development, curriculum accommodation, and creation of equitable learning environments to promote metacognition across learner contexts. This work further enriches the discussion on metacognition by drawing attention to specific practical approaches and underlining the importance of continuing support mechanisms in learning.